Does Personalisation Promote Learners’ Attention? An Eye-Tracking Study - Zander, Steffi; Reichelt, Maria; Wetzel, Stefanie; Kämmerer, Frauke; Bertel, Sven (Frontline Learning Research, 2015)
The personalisation principle is a design recommendation and states that multimedia presentations using personalised language promote learning better than those using formal language (e.g., using ‘your’ instead of ‘the’). It is often assumed that this design recommendation affects motivation and therefore allocation of attention. To gain further insight into the processes underlying personalisation effects we conducted an eye tracking experiment with 37 German university students who were presented with either personalised or formal learning materials. We examined group differences in attention allocation parameters (fixation count, fixation duration, transition count). The eye-tracking data was combined with self-reports concerning motivation, cognitive load, and learning outcomes. Eye-tracking data revealed a significantly higher reading depth for the main picture areas of interest in the personalised condition. Additionally, participants found the personalised version more appealing and inviting. For learning outcomes, there was a significant positive effect of personalisation for retention, not for transfer. We discuss additional explanatory variables as well as methodological and practical implications for instructional design.